Administration of GDF3 Into Septic Mice Improves Survival via Enhancing LXRα-Mediated Macrophage Phagocytosis - Wang, Peng; Mu, Xingjiang; Zhao, Hongyan; Li, Yutian; Wang, Lu; Wolfe, Vivian; Cui, Shu-Nan; Wang, Xiaohong; Peng, Tianqing; Zingarelli, Basilia; Wang, Chunting; Fan, Guo-Chang (Frontiers in Immunology, 2021)
The defective eradication of invading pathogens is a major cause of death in sepsis. As professional phagocytic cells, macrophages actively engulf/kill microorganisms and play essential roles in innate immune response against pathogens. Growth differentiation factor 3 (GDF3) was previously implicated as an important modulator of inflammatory response upon acute sterile injury. In this study, administration of recombinant GDF3 protein (rGDF3) either before or after CLP surgery remarkably improved mouse survival, along with significant reductions in bacterial load, plasma pro-inflammatory cytokine levels and organ damage. Notably, our in vitro experiments revealed that rGDF3 treatment substantially promoted macrophage phagocytosis and intracellular killing of bacteria in a dose-dependent manner. Mechanistically, RNA-seq analysis results showed that CD5L, known to be regulated by liver X receptor α (LXRα), was the most significantly upregulated gene in rGDF3-treated macrophages. Furthermore, we observed that rGDF3 could promote LXRα nuclear translocation and thereby, augmented phagocytosis activity in macrophages, which was similar as LXRα agonist GW3965 did. By contrast, pre-treating macrophages with LXRα antagonist GSK2033 abolished beneficial effects of rGDF3 in macrophages. In addition, rGDF3 treatment failed to enhance bacteria uptake and killing in LXRα-knockout (KO) macrophages. Taken together, these results uncover that GDF3 may represent a novel mediator for controlling bacterial infection.